Promotion of Physical Activity Using Point-of-Decision Prompts in Berlin Underground Stations - Müller-Riemenschneider, Falk (Molecular Diversity Preservation International (MDPI), 2010)
To evaluate point-of-decision prompts in the promotion of stair use in Germany, motivational posters were placed at three underground stations in Berlin. The proportion of passengers using stairs or stairways was counted before, during installation, and two weeks after removal of posters. In total, 5,467 passersby were counted. Stair use increased significantly in women, but not in men. The present pilot study thereby shows that the use of point-of-decision prompts is also feasible in Germany and it provides some evidence of effectiveness. Methodologically rigorous studies are warranted to confirm these findings.